Model for Presenting Financial Reports of Non-Profit Organizations at Educational Foundations - Akhmad Noval Adzani; Ana Sopanah; Dwi Anggarani (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The purpose of this research is to determine the process of preparing financial reports presented by the Foundation. Apart from that, it is also to present financial reports to the Foundation using the basis of ISAK (Interpretation of Financial Accounting Standards) 35. This research was conducted at the Al-Hidayah Kindergarten Education Foundation, Pasuruan City, East Java, Indonesia. The type of research used in this research is descriptive qualitative, using primary and secondary data. The informants in this research were the person in charge, secretary, and financial manager or treasurer. After conducting research at the Al-Hidayah Kindergarten Education Foundation, Pasuruan City, there were several conclusions that answered the questions in the research focus. The Al-Hidayah Kindergarten Education Foundation, Pasuruan City has not used the appropriate basis, namely ISAK 35, in its reporting, this is due to the lack of knowledge possessed by the finance department in providing financial information in accordance with applicable standards.